Development of educational software for stress analysis of an aircraft wing - Mohamed Ali, Jaafar Syed; Sadeq, Tazkera (Taylor's University, 2012)
A stress analysis software based on MATLAB, Graphic user interface (GUI) has been developed. The developed software can be used to estimate load on a wing and to compute the stresses at any point along the span of the wing of a given aircraft. The generalized formulation allows performing stress analysis even for a multispar (multicell) wing. The software is expected to be a useful tool for effective teaching learning process of courses on aircraft structures and aircraft structural design.